Karakteristik Klinikopatologik serta Hubungan Derajat Keganasan dengan Subtipe Molekular Luminal B pada Pasien Karsinoma Payudara di RSUP Mohammad Hoesin Palembang Tahun 2014-2016 - Reihan Putri Awaliah; Citra Dewi; Riana Sari Puspita Rasyid (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2022)
BackgroundBreast carcinoma is the second highest malignant disease that causes death in Indonesia with 58,256 new cases in 2018. LuminalB has more aggressive clinical behavior and is considered as having unfavorable prognosis. This study aimed to determine theclinicopathological characteristics and the relationship histological grade with breast carcinoma subtype molecular luminal B.MethodsThis is a descriptive analytic study with cross sectional design using secondary data of breast carcinoma patients registered atRSUP Mohammad Hoesin Palembang during the period of January 1st, 2014 to December 31st, 2016.ResultsFrom 903 breast carcinoma patients in Mohammad Hoesin Hospital Palembang during 2014 to 2016, 43.63% had luminal Bmolecular subtype. The highest incidence and prevalence washappened in year 2016, whichwere 4.7 and 4.4 per 10 breastcarcinoma patients, respectively. The majority of breast carcinoma of luminal B molecular subtype occurs in the group of patientsaged ≥40 years (81.7%), female (98.7%), Malay race (100%), marital status (98.8%), housewives (68.3%), histopathologicalcarcinoma of invasive non-specific type (75.9%), high grade/ grade III (63.7%), localized (60.6%), no metastases (60.0%), rightsided tumor laterality (50.8%) and with negative HER2 (65.2%). There was a significant relationship between the histopathologicalgrade and breast carcinoma luminal B molecular subtype (p=0.009).ConclusionThe incident of breast carcinoma molecular subtype luminal B at Mohammad Hoesin Hospital Palembang has increased in the lastthree years with the poor clinicopathological characteristics.